Organisation matters: towards an organisational sociology of science communication. Issue 3 (12th March 2020) - Rödder, Simone
Abstract : Purpose: This paper looks at science communication through an organisational lens with the aim of assessing the relevance of different organisational forms for science communication. Design/methodology/approach: The paper explores science communication in different organisational forms. Based on conceptual considerations and by reviewing existing empirical literature, the paper selects and compares three organisational forms of science communication: the editorial office of a daily newspaper, the press office of a university and the Science Media Centre. Findings: The paper shows the relevance of organisation for science communication by comparing three organisational forms. The first two, the science news desk and the press office, have the character of a sub-system of an organisation, while the third, the Science Media Centre, forms its own organisation. The paper shows how the respective set-up shapes science-media contacts with a focus on the occurrence and resolution of conflicts. Research limitations/implications: The paper proposes a conceptual framework for studying science communication through an organisational lens but leaves comparative empirical studies of all types to future research. Yet, it outlines and compares implications of the formal organisation of science communication from a conceptual point of view. Practical implications: The findings provide information on the structural impact of different organisational forms on science communication and point to where conflicting expectations, and thus potential conflicts, are most likely to occur in each case. A reflection of structurally conflicting expectations and how they can be overcome in specific situations is of high practical value for all science communication activities. Originality/value: Organisational theorists have long argued that organisations are the key to understanding society. Despite their undoubted relevance, however, organisations and their influence on science communication have so far been much less analysed – both conceptually and empirically – than its contents, its practices and its impacts on public understanding, public policy, and on science and scientists. The paper contributes to the emerging field with conceptual considerations towards an organisational sociology of science communication.